Influences of occupational therapy as curricular activity on to psychophysical development of hearing-impaired students - Oana Rusu; Demmy Rusu (Exercise and Quality of Life)
We intend to identify the effects of the occupational therapy means on self-esteem and on the psychomotor development level for hearing-impaired students. Two instruments (test-retest at an 18month interval) have been used for the hearingimpaired pupils of the “VasilePavelcu” Technological Special High School in Iasi: the scale of multidimensional attitudes for self-esteem E.T.E.S. (N=45 subjects, 24 boys and 21 girls, aged between 13 and 18) in elementary and high school, each groups of 15 subjects; the test Ozeretski – Guillmain (N= 45 de subjects: 25 boys and 20 girls, aged between 8 and 12) in primary and elementary school. Individual test applied for assessment of pshycho-motor development level. The subjects for whom we have assessed the self-esteem attended activities that included pantomime / puppet theater, manual and sports skills activities. The subjects for whom we have assessed the psycho-motor development level have attended the following activities: manual skills, painting, and sports activities. All activities were attended following a preset graph. There is a significant statistical difference to subjects in the phase of retesting to the testing phase for all the variables taken into account: social self-esteem, prospective self-esteem, total level of psycho-motor development. Self-esteem  and the level of psycho-motor development are two variables that can improve the psychophysical state of children with hearing impairment through occupational therapy. Under its various forms, it can be a tool used by and in school to achieve socio-professional integration, but also training and personal development.